Performances of Pentacene OFETs Deposited by Arbitrary Mounting Angle Vacuum Evaporator - Shen, Xueli; Wang, Yandong; Li, Jianping; Chen, Yangkai; Wang, Zhifang; Wang, Wenchong; Huang, Lizhen; Chi, Lifeng (Frontiers in Materials, 2020)
Vacuum evaporator is widely used for generating atomic/molecular beams for thin film deposition, and conventionally must be mounted to a vacuum chamber with an upwards angle from the horizontal. In this article, we report a novel kind of evaporator that can be mounted at an arbitrary angle for organic materials. The crucible of the evaporator here is designed to keep the loaded organic materials from falling down. The morphology and electrical characteristics of pentacene thin film OFETs on OTS modified SiO2 are characterized and compared for commercial and arbitrary mounting angle evaporators. Pentacene films deposited from both evaporators exhibit similar morphology and domain size characterized by AFM, as well as similar mobility, threshold voltage and on/off ratio. The results can be used to develop a new configuration of organic vacuum deposition system, which allows positioning shadow masks directly on substrates and thus avoids deformation, enabling fabrication of organic electronics for high resolution over large areas.